Migration and Social Protection in Europe and Beyond (Volume 2) Comparing Consular Services and Diaspora Policies - Lafleur, Jean-Michel; Vintila, Daniela (IMISCOE Research Series, 2020)
This second open access book in a series of three volumes examines the repertoire of policies and programmes led by EU Member States to engage with their nationals residing abroad. Focusing on sending states' engagement in the area of social protection, this book shows how a series of emigration-related policies that go beyond the realm of social security address the needs of nationals abroad in the area of health care, unemployment, family benefits, pensions and economic hardship. In addition, this volume highlights the variety of sending states' institutions that are involved in these policies (consulates, diaspora institutions, ministries, agencies...) and their engagement with citizens abroad in other policy areas such as electoral rights, citizenship, language, culture, education, business or religion. As such this book is a valuable read to researchers, policy makers, government employees and NGO's.